PENGARUH AGRESIVITAS PAJAK TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR SEKTOR PERTANIAN SUBSEKTOR PERKEBUNAN DI BEI) - Heny Sidanti; Vivi Cornaylis (Universitas PGRI Madiun, 2018)
This study aims to provide empirical evidence about the effect of tax aggressiveness on corporate value with profitability as a moderating variable (empirical study of manufacturing companies in the agricultural sector of the estate sub-sector in BEI). The type of research used in this study is quantitative research. Population in this research is manufacturing company of agricultural sub-sector of plantation at BEI 2012-2016. There are 7 sample in this research which were taken by using purposive sampling methode. Data analysis used were descriptive statistic, classical assumption test, multiple linear regression, and hypothesis test using SPSS version 17.0. partial test results (t test), tax aggressiveness doesn’t affect on corporate value. While the results of the moderation t test, profitability can’t moderate the influence of tax aggressiveness on corporate value.